Evaluation of the effectiveness of psychoeducation in the structure of rehabilitation of patients with bipolar affective disorder - Rezunenko, Oleg (ScienceRise: Medical Science, 2017)
Aim of research: The assessment of the effectiveness of psychoeducational programs in the complex psychosocial rehabilitation of patients with a bipolar affective disorder. Materials and methods. The study includes the complex clinical-psychopathological, clinical-anamnestic and psychodisgnostic examination of 158 patients with BAD. The main group (which patients took part in the psychoeducational program) included 94 persons. The control group consisted of 64 patients, who received the standard regulated therapy at a hospital. Results of research. There were elaborated the algorithm of the psychoeducational work that includes the use of different information modules, holds of the cognitive-behavior psychotherapy, training interactions (positive self-attitude, compliance improvement, formation of communicative abilities and skills, solution of problems of interpersonal interaction), problem-oriented discussions and also family psychotherapy. The high effectiveness of psychoeducation comparing with the traditional complex treatment and rehabilitation of patients with BAD as to the reduction of psychopathological symptomatology, activation of adaptive coping-strategies, transformation of maladjustment types of an attitude to a disease into adaptive ones, patients’ life quality improvement was established. Conclusions: The offered system of psychoeducation of patients with BAD demonstrated the high effectiveness comparing with the traditional rehabilitation complex